Identification Affecting Factors of Price Discount Threshold: Meta Synthesis - Hamidreza Biranvand; Mohsen Nazari (‫مدیریت بازرگانی, 2020)
Objective Competitiveness of business environment in the country, growth of ever-discount stores, and the prevalence of foreign brands in the form of stores and shopping centers in Tehran and other cities have caused Iranian stores and companies to widely develop their price discounts so as to increase their sales and expand their market share. In this new space, if the strategy and methods of discounting are not used effectively, that is, the percentage of discount is too high or too low, the time and repetition of the discount is high or low, and etc., Iranian stores and companies will face several risks including reduced sales, weakening of the brand’s position, and so on. Hence, the present study aims to explore for the factors influencing these levels, which are referred to as the "price discount threshold" in this study. The main purpose is, then, to identify which factors affect the high and low discount threshold to use those effective strategies. This research helps stores and companies design a "discount window".   Methodology This research is developmental in terms of purpose, qualitative in terms of the data analysis research and documentary in terms of data collection method. The present study is analytical-descriptive in terms of research method. This study was conducted through meta-synthesis. For this purpose, after CASP analysis, 24 studies that have directly addressed the issue of discount threshold entered the analysis phase. The selected researches were entered into Max Kioda software for codification and were using Max Kioda software.   Findings In this study, 24 studies directly dealt with the discount threshold entered the analysis phase. Finally, after the integrations phase, 56 distinct codes were identified. In the next step, the codes were identified in the form of 23 concepts or themes and finally the concepts were identified in the form of 13 categories as affecting factors on the price image based on the results of the identification analysis and their quality test. Based on the findings, the “brand” with 16 citations, the “discount percentage” with 12 citations, the “type of products” with 9 citations, the “repetition of discount” with 5 citations, and the “reference price” with 4 citations were among the most important codes in terms of citation. As mentioned earlier, the identification of the themes and categories of this model has been finalized in the fifth stage of the analysis.   Conclusion In this study, for the first time, the affective factors on the discount threshold for the prices were examined using meta-combination method in shopping centers. According to the evaluated studies, the dimensions such as product brand, discount percentage, type of product, repetition of discount and reference price were identified as having the most impact (referrals).